Microstructural analysis of N-polar InGaN directly grown on a ScAlMgO4(0001) substrate. (1st June 2022) - Velazquez-Rizo, Martin; Najmi, Mohammed A.; Iida, Daisuke; Kirilenko, Pavel; Ohkawa, Kazuhiro
Abstract: We report the characterization of a N-polar InGaN layer deposited by metalorganic vapor-phase epitaxy on a ScAlMgO4 (0001) (SAM) substrate without a low-temperature buffer layer. The InGaN layer was tensile-strained, and its stoichiometry corresponded to In0.13 Ga0.87 N. We also present the microstructural observation of the InGaN/SAM interface via integrated differential phase contrast-scanning transmission electron microscopy. The results show that the interface between N-polar InGaN and SAM occurs between the O atoms of the O–Sc SAM surface and the (Ga, In) atoms of InGaN.